How much genetic information in RNA form can be protected by a CCMV virus-like particle? - Ana Luisa Duran Meza; Sophie-Christine Porak; Abigail Chapman; Charles M. Knobler; William M. Gelbart (PLoS ONE, 2025)
The capsid protein of cowpea chlorotic mottle virus (CCMV) has been used extensively for in vitro packaging of heterologous RNA. The associated virus-like particles (VLPs) are spherical with a 3nm-thick/28nm-diameter protein shell and are therefore limited in the amount of RNA they can package. As shown in earlier work, when RNA lengths are longer than ~3500nt the RNA is no longer self-assembled exclusively into a single VLP. Rather, it is shared by two or more 28nm-diameter capsids in the form of doublets, triplets, and higher-order multiplets, with the RNA threaded through the naturally- occurring ~1.5nm-diameter holes in the 180-subunit/icosahedrally-symmetric protein shells. Consistent with this fact we find in the present work that 3500nt is the maximum length of packaged RNA that is fully protected under strong RNase digestion conditions.